2005
DOI: 10.1016/j.femsre.2005.04.008
|View full text |Cite
|
Sign up to set email alerts
|

New insights in the molecular biology and physiology of revealed by comparative genomics

Abstract: Streptococcus thermophilus is a major dairy starter used for the manufacture of yoghurt and cheese. The access to three genome sequences, comparative genomics and multilocus sequencing analyses suggests that this species recently emerged and is still undergoing a process of regressive evolution towards a specialised bacterium for growth in milk. Notably, S. thermophilus has maintained a well-developed nitrogen metabolism whereas its sugar catabolism has been subjected to a high level of degeneracy due to a pau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
368
1
14

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(406 citation statements)
references
References 198 publications
(206 reference statements)
18
368
1
14
Order By: Relevance
“…L. plantarum strains showing a high-CO 2 -requiring auxotroph are able to synthesize sufficient arginine and pyrimidines in CO 2 -enriched air only. Unlike L. plantarum, S. thermophilus has only one CpS, which is encoded by a carB gene (Hols et al, 2005), and this represents a key node in arginine and pyrimidine biosynthesis (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…L. plantarum strains showing a high-CO 2 -requiring auxotroph are able to synthesize sufficient arginine and pyrimidines in CO 2 -enriched air only. Unlike L. plantarum, S. thermophilus has only one CpS, which is encoded by a carB gene (Hols et al, 2005), and this represents a key node in arginine and pyrimidine biosynthesis (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Conjugative transposons are one of the main drivers of gene gain and loss, and therefore if the lack of transposases in strain MG1 truly reflects a low level of genome plasticity, this could indicate the stable adaptation of this strain to its sourdough niche (Douillard & de Vos, 2014;Hols et al, 2005). However, the low number of transposases in these strains of W. cibaria is in stark contrast to the 111 found in another sourdough LAB, Lactobacillus sanfranciscensis TMW 1.1304, in which it was suggested that their high number facilitated niche adaptation of this strain (Vogel et al, 2011).…”
Section: Genomics Of Weissellamentioning
confidence: 99%
“…Besides Lactococcus lactis, Streptococcus thermophilus is the second most widely used lactic acid bacterium in the industrial manufacture of fermented food products. The market value of S. thermophilus is estimated to be around 40 billion US dollars with a scale of over 10 21 live cells per year for human consumption (De Vuyst and Tsakalidou, 2008;Hols et al, 2005). Rasic and Kurmann (1978) has reported the crucial role of S. thermophilus in producing the aromatic compounds in fermented milk products, while Beshkova et al (1998) supported Lactobacillus delbrückii subsp.…”
Section: Introductionmentioning
confidence: 99%